"No Bourgeoisie, No Democracy"? The Political Attitudes of the Kenyan Middle Class. (15th July 2015) - Cheeseman, Nic; Resnick, Danielle
<x xml:space="preserve">Abstract</x> Barrington Moore's famous line 'no bourgeoisie, no democracy' is one of the most quoted claims in political science. But has the rise of the African middle class promoted democratic consolidation? This paper uses the case of Kenya to investigate the attitudes and behaviours of the middle class. Analysis of Afrobarometer survey data reveals that the middle class is more likely to hold pro‐democratic attitudes. This suggests that Moore's argument deserves to be taken seriously, at least in some African countries, and that contemporary demographic changes will improve the prospects for democratic consolidation. However, qualitative evidence from the Kenyan 2013 general election raises important questions about the resilience of these attitudes. The middle class may be more inclined to democratic attitudes than their less well‐off counterparts, but class continues to intersect with ethnicity, and its political salience is likely to wax and wane as a result. © 2015 The Authors. Journal of International Development published by John Wiley & Sons, Ltd.